Reciprocal regulation of rumen microbiota and epithelial genes in response to small peptide supplementation for feed efficiency in beef cattle - Liu, En; Sun, Shujun; Deng, Yawen; Liu, Jiajia; Xue, Jintao; Li, Mengmeng; Xue, Fuguang (Frontiers in Veterinary Science, 2026)
IntroductionBeef cattle during the finishing phase are predominately fed with high-cereal diets to promote rapid growth, which commonly caused surplus energy supply and nitrogen deficiency, disrupted rumen energy and nitrogen balance (RENB), and reduced feed efficiency. This study aims to determine the effects of small peptide (SP) supplement on reciprocal patterns between rumen microbiota and epithelial genes in regulating nutrient metabolism and feed efficiency of beef cattle.MethodsA total of sixty 12-month-old Simmenthal male beef cattle with the non-significant initial body weight were randomly assigned into the control treatment and arithmetically increased SP additional (0.2%, 0.4%, 0.6%, 0.8% and 1.0%) treatments. Each treatment contains 10 bulls with each bull was considered as one replicate. Growth performances, nutrient digestibility, rumen fermentable parameters, rumen microbiota, and rumen epithelial gene expressions were detected to determine the effects of SP on beef cattle.Results and discussion0.6% and 0.8% of SP supplement showed the highest average daily weight gain (ADG), neutral detergent fiber (NDF) digestibility, and the lowest feed conversion ratio (FCR) among all treatments, which showed significant discrepancies compared with CON treatment (P < 0.05). Additionally, 0.6% of SP supplement treatment showed a significant higher content of acetate, and acetate/propionate ratio compared with 0.8% and CON treatments(P < 0.05). Therefore, 0.6% of SP supplement treatment was considered as the optimum supplement level and applied for further microbial and rumen epithelial gene expression analysis. SP supplement significantly increased the Alpha diversity and relative abundances of the Acetitomaculum, Butyrivibrio, Pseudobutyrivibrio, Bifidobacterium, and Butyricicoccus (P < 0.05), while decreased the Saccharofermentans, and Selenomonas (P < 0.05). Rumen epithelial results showed SP supplement up-regulated genes of ATP10B, ACSF2, ADGRG6, and GALNT15, while down-regulated genes of ABCC3, GEM, PDK2, and ADIRF. The differential expressed genes mainly enriched into the catalytic activity, pyruvate metabolism, metabolic pathways, protein digestion and absorption pathways. Conclusion. These findings demonstrate that SP supplementation enhances growth performance and rumen function and provide a viable nutritional strategy for improving feed efficiency in finishing beef cattle.